The cost of poverty alleviation transfer programs: a comparative analysis of three programs in Latin America - Caldés, Natàlia; Coady, David; Maluccio, John A. (International Food Policy Research Institute, 2004)
This paper proposes and implements a methodology for a detailed, comparative analysis of the level and structure of costs for three similar poverty alleviation programs in Latin America: the Programa Nacional de Educación, Salud y Alimentación (PROGRESA) in Mexico, the Programa de Asignación Familiar-Fase II (PRAF) in Honduras, and the pilot Red de Protección Social (RPS) in Nicaragua. These innovative programs target cash transfers to the poorest communities and households, and condition them on attendance at school and health clinics. This conditionality effectively transforms the cash transfers into human capital subsidies for poor households.